English Adventure: Strategi Pembelajaran Bahasa Inggris untuk Sekolah Dasar di Desa Botubarani - Reza Dwi Julianto Mohama; Nurul Istiqamah Kadekoh; Sri Rahmawati Kono; Muly Nursia Abdjul; Wahyu Ramadhan Harmain; Magdalena Baga (Ideas Publishing, 2022)
English languange learning in children who have not mastered basic English on Botubarani village is needed, because the village is an Internasional tourism village. This study aimed tofind out the achievement of English learning strategy based English Adventure implementation of students English skills development on SD Negeri Kabila Bone. This study used language acquisition theory then using observation and descriptive analysis method to describe the phenomena occur in the classroom. After 8 intensive meetings, the students looked more motivated to learn, they could recognized, wrote, and memorized English vocabularies they heard in the film, also could answer the questions correctly.